A Comparative study of the combustion characteristics of rubberwood and some Malaysian wood species - Tan A G; Scott J B (Journal of Natural Rubber Research, 1987)
The combustion characteristics of rubberwood and eighteen common Malaysian wood species were examined and compared using two complementary methods of analysis, namely differential thermal analysis (DTA) and thermogravimetry (TG). The DTA experiments were carried out in fluidised beds, as opposed to static beds in the conventional method. The results obtained indicate that rubberwood is relatively easy to burn and that, in general, the lighter a wood species, the easier it is to burn. Incresing the oxygen supply to the combustion chamber resulted in the wood burning faster but did not seem to have a major effect on its relatively combustibility. The effects of ash and moisture content of the wood on its combustion were discussed.
Keywords: Rubberwood